Research Data Management and Sharing Practices in the Digital Humanities with a Focus on Publisher Support: A Case Study in the Field of Web Archive Studies - Truter, Victoria Zea (Library and Information Studies Centre (LISC), 2022)
The research problem at the centre of this study is twofold. First, not enough Research Data Management studies have been conducted in either the humanities or the Digital Humanities that present a well-developed understanding of the nature of data in these fields, or the appropriate management thereof. Second, there is a critical lack of Research Data Management and data sharing support provided to researchers in these fields. While multiple stakeholders play roles in providing such support, this study focuses on the support provided to researchers by publishers. While the overarching study investigates data management and sharing in the Digital Humanities and how publishers support these practices, the specific case concerns the field of Web Archive Studies. The case study also gathers broader insights into Digital Humanities researchers, under which WAS is classified as a specialised field. The purpose of the study was to explore the nature of data, and current RDM and data sharing practices of Web Archive Studies researchers, with a focus on publishers' engagement with researchers and support for said practices. The aim was to uncover ways in which publishers might better support Web Archive Studies researchers in managing and sharing their data. The case study answered the following research questions: (1) ‘What kinds of data do Web Archive Studies researchers generate and work with?'; (2) ‘What RDM and data sharing practices do these researchers tend to use?'; (3) ‘What challenges and limitations do they encounter when collecting, managing, and sharing data?'; (4) ‘How can publishers better support Web Archive Studies researchers in managing and sharing their data?'. The study is exploratory in nature and uses a convergent mixed-methods approach based within an interpretive paradigm. Three semi-structured interviews (using predominantly open-ended questions) and a questionnaire (including predominantly multiple-choice questions) were conducted. A content analysis approach was used to analyse qualitative data, while quantitative data were interpreted using inferential statistics. The populations sampled included publishers and Web Archive Studies researchers. The study found that Web Archive Studies researchers tend to manage their data proficiently. The biggest gaps in their current practices concern data sharing in formal repositories due to challenges like legal restrictions. Additional findings reveal a lack of funding for Research Data Management and data sharing in this field, as well as a lack of guidance and training from publishers for Web Archive Studies researchers. Information Classification: General Key recommendations include the following: (1) publishers should develop guidance specific to Web Archive Studies researchers' RDM and data sharing needs; (2) publishers should focus on sharing methodological processes, audit trails, and research instruments, rather than sharing data for Web Archive Studies and other humanities subjects. These actions would promote transparency in subject areas for which data sharing is often not possible due to legal restrictions, among other challenges.